Spatial distribution of decayed and restored teeth in an adult population - Manoelito Ferreira SILVA-JUNIOR; Emílio Prado da FONSECA; Marília Jesus BATISTA; Maria da Luz Rosário de SOUSA (Faculdade São Leopoldo Mandic, 2019)
Objective: To analyze the spatial distribution of decayed and restored teeth in adults according to the Social Exclusion Index (SEI) and the proximity of public dental service. METHODS: This ecological study used secondary data from an epidemiological survey of oral health and from the Piracicaba Research and Planning Institute (IPPLAP). The oral examinations of the DMFT index examined in households by a single examiner calibrated in 2011, by probability sampling, 248 adults (aged 20 to 64 years) representing the residents in Piracicaba-SP, Brazil. Data on social exclusion and health units with dental service were extracted from IPPLAP. We performed georeferencing of the census tracts selected by draw in the epidemiological survey and their respective districts, in addition to the health units with dental service in a radius of 500 m and 1000 m. Spearman's rank correlation coefficient was analyzed (p<0.05). RESULTS: The smallest value of SEI, that is, the highest social exclusion, showed no correlation with decayed teeth (p=0.09), but had strong positive correlation with restored teeth (r=0.79; p<0.0001). Presence of public dental service in the vicinity of 500 m and 1,000 m showed no correlation, respectively, with the average number of decayed (p=0.07 and p=0.58) and restored (p=0.26 and p=0.56) teeth. CONCLUSION: Although the correlation between social exclusion and caries in adults was not observed, its case management, namely, the restored teeth, showed correlation with social inequalities. Presence of public dental service showed no correlation with components of caries experience evaluated in this study.